Importance of Business Ethics in the Employees of the Corrales Corporation - Lima, 2022 - Seminario Unzueta, Randall Jesús (2022)
Objective: to describe the business ethics in the collaborators of the CORRALES Lima corporation - 2022. Material and method: the study of this research is focused on a quantitative approach, of a cross-section and it is even a non-experimental investigation; In view of the fact that it is an investigation that does not intentionally vary the autonomous variable to visualize its effect on others, it is also descriptive, that is why the phenomenon will only be observed as it is in its natural form, to then analyze it. For this study, a population of 50 employees is considered, with a sample size of 45 employees. Results: when applying descriptive statistics, it was determined that in the CORRALES Lima - 2022 corporation; only 51.11% stated that sometimes ethics is reflected in the company; In addition, 33.3% stated that an adequate management of the business management is almost never reflected, with respect to delegating functions and establishing purposes so that the company can develop and generate continuous growth; even 57.8% stated that sometimes it is reflected that the company demonstrates the entrepreneurial function; only 82.2% stated that bad business decisions were hardly ever made. Conclusions: the results have shown that all of the 45 employees of the company CORRALES SAC sometimes show adequate ethics depending on the company.